Insecticide and Repellent Mixture Pour-On Protects Cattle against Animal Trypanosomosis. - Geoffrey Gimonneau; Yaya Alioum; Mamoudou Abdoulmoumini; Andre Zoli; Bylah Cene; Hassane Adakal; Jérémy Bouyer (Public Library of Science (PLoS), 2016)
BACKGROUND:African animal trypanosomosis (AAT), transmitted by tsetse flies and tick-borne diseases are the main constraints to livestock production in sub-Saharan Africa. Vector control methods such as pour-on offer individual protection against ticks but not against tsetse so far, for which protection has always been communal, through a reduction of their density. The latter requires the treatment of a large part of the herd in a given landscape and is not instantaneous. METHODOLOGY/PRINCIPAL FINDINGS:Two prospective surveys were conducted to evaluate the efficacy and persistence of a pour-on formulation composed of cypermetrhin, chlorpyrifos, piperonyl butoxid and citronella (Vectoclor, CEVA Santé Animal). In experimental conditions, tsetse flies were exposed to treated and control cattle. Flies knockdown and engorgement rates were determined and the product persistence was assessed as the time for these parameters to drop below 50% (T50). T50 was 37 days (95%CI: [33-41] days) and 46 days (95%CI: [39-56] days) for the knockdown and engorgement rates respectively. In field conditions, two cattle herds were monitored following a case-control experimental design, in the Adamaoua region of Cameroon. One herd was treated once with Vectoclor pour-on (treated group) and the second used as a control group (not treated). Ticks infestation rate, trypanosomosis prevalence and packed-cell volume were measured over the two months following treatment. The treatment was highly effective against ticks with a complete elimination three days after application in the treated group. Trypanosomosis prevalence was also significantly reduced during the study (by 4, P<0.001) and PCV of the treated group increased significantly in the same time (P<0.001), contrary to the control group. CONCLUSIONS/SIGNIFICANCE:The protection of this new pour-on against tsetse bites and trypanosomosis is demonstrated here for the first time. Moreover, this insecticide and repellent mixture offer a longer persistence of the efficacy against both tsetse and ticks than similar products currently on the market. It offers a great new opportunity for an integrated AAT control strategy including the treatment of residual cases with trypanocides. It might also allow controlling the spread of resistance against these trypanocides.